Incidence, prevalence, and hybrid approaches to calculating disability-adjusted life years - Schroeder S (BMC, 2012)
Abstract When disability-adjusted life years are used to measure the burden of disease on a population in a time interval, they can be calculated in several different ways: from an incidence, pure prevalence, or hybrid perspective. I show that these calculation methods are not equivalent and discuss some of the formal difficulties each method faces. I show that if we don't discount the value of future health, there is a sense in which the choice of calculation method is a mere question of accounting. Such questions can be important, but they don't raise deep theoretical concerns. If we do discount, however, choice of calculation method can change the relative burden attributed to different conditions over time. I conclude by recommending that studies involving disability-adjusted life years be explicit in noting what calculation method is being employed and in explaining why that calculation method has been chosen.